Late Pleistocene glaciation history of the southern Black Forest, Germany: 10Be cosmic‐ray exposure dating and equilibrium line altitude reconstructions in Sankt Wilhelmer Tal. (14th January 2022) - Hofmann, Felix Martin; Preusser, Frank; Schimmelpfennig, Irene; Léanni, Laëtitia; Aster team (Georges Aumaître, Karim Keddadouche & Fawzi Zaidi),
ABSTRACT: During the Late Pleistocene, an ice cap temporarily rested on the highest summit of the Black Forest, Feldberg, and on the surrounding region. Moraines inside the last glaciation maximum ice extent document subsequent glacial standstills and/or re‐advances, but the chronology of the deglaciation remains largely unknown. In Sankt Wilhelmer Tal, moraines were mapped, and suitable moraine boulders were sampled for 10 Be cosmic ray exposure (CRE) dating. Equilibrium line altitudes (ELAs) during moraine formation were reconstructed to evaluate whether these can be used for local stratigraphical correlations. Geomorphological mapping revealed numerous ice‐marginal positions in the main valley and in two tributary valleys. CRE ages and ELAs indicate two discrete phases of glacial standstills and/or re‐advances by 17–16 ka at the latest and no later than 14 ka, respectively. Differing ELAs across the study area preclude the use of ELAs for local stratigraphical correlations. Recalculated 10 Be CRE ages from other localities in Central Europe indicate similar periods of moraine formation, thus raising the question of a common climatic forcing. Additional sets of CRE ages are needed to answer this question. In addition, future studies should concentrate on determining the age of the last glaciation maximum in the Black Forest.